2010
DOI: 10.1097/tp.0b013e3181d21e7f
|View full text |Cite
|
Sign up to set email alerts
|

Use of Intravenous Immune Globulin and Rituximab for Desensitization of Highly HLA-Sensitized Patients Awaiting Kidney Transplantation

Abstract: BACKGROUND.: We have shown that high-dose intravenous immune globulin (IVIG; 2 g/kg x2 doses)+rituximab (1 g x2 doses) was effective in lowering anti-human leukocyte antigen (HLA) antibodies and improving rates of transplantation. The aim of this report was to evaluate the efficacy of IVIG+rituximab on reduction of anti-HLA antibodies to a level that was permissive for living donor (LD) or deceased donor (DD) transplantation without incurring the risk of antibody-mediated rejection and immediate graft loss. ME… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
163
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(171 citation statements)
references
References 33 publications
6
163
2
Order By: Relevance
“…Some authors have reported good outcomes using rituximab, PEX, and IVIG, which are effective in the treatment of rejection in immunologically high-risk patients. [11][12][13][14][15] These 3 methods were designed to inhibit existing antibodies. Rituximab is a chimeric anti-CD20 (anti-B cell) monoclonal antibody approved for the treatment of lymphoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors have reported good outcomes using rituximab, PEX, and IVIG, which are effective in the treatment of rejection in immunologically high-risk patients. [11][12][13][14][15] These 3 methods were designed to inhibit existing antibodies. Rituximab is a chimeric anti-CD20 (anti-B cell) monoclonal antibody approved for the treatment of lymphoma.…”
Section: Discussionmentioning
confidence: 99%
“…Good outcomes using rituximab, plasma exchange (PEX), and intravenous immunoglobulin (IVIG) have been reported in immunologically high-risk patients. [11][12][13][14][15] We achieved better outcomes using a unique protocol that combined these methods including the use of retuximub, PEX, and IVIG in patients who were FCXM-positive for both T and B cells (FCXM T+B+). In the present study, we investigated the clinical course of FCXM T+B+ patients to validate our strategy.…”
Section: Introductionmentioning
confidence: 99%
“…In these studies rejection rates were 31-59% and patient and graft survival was 96-100% and 75-100% respectively. Four of the studies included rituximab as a part of their pre-transplant conditioning regimens [62][63][64][65]. Despite the addition of rituximab, AMR rates remained high, 37-50% and patient and graft survival were similar to the IVIG alone groups 86-100% and 79-94% respectively.…”
Section: Modulation Of the Immune Response In Recipients With Crossmamentioning
confidence: 99%
“…In this cohort, desensitized patients waited for an additional 4.2±4.5 months before receiving a deceased donor graft. Overall graft failure and death at 2 years were 80% and 91% respectively, but almost 30% of graft loss was directly attributed to AMR (Vo, Peng et al 2010). …”
Section: Desensitization Of Highly-sensitized Patients On Deceased Domentioning
confidence: 99%